The silence of the huia: Bird extinction and the archive. Issue 2 (1st October 2019) - Boyle, Cameron
AbstractIn this article, I argue that art can enable a critique of museological conventions, along with related ideas of natural history and extinction, which together have structured practices of preserving and representing departed species as scientific specimens. I draw on the case of the huia specifically, a bird species endemic to New Zealand, which became extinct in the early twentieth century, as a result of multiple ecological, cultural, political and economic forces stemming from colonization. I suggest the preservation of individual huia birds in the form of scientific specimens demonstrates how Victorian aesthetics and ideas about the natural world shaped the modality through which non-human life was, and to some extent still is, recorded and portrayed according to particular archival norms. Utilizing concepts from recent scholarship in the field of extinction studies, I critically consider how the works of two artists which feature the huia, challenge the traditions of the museum and the archive. First, I examine how Fiona Pardington's photography of huia specimens frames the species as a life form that became extinct in a context scarred by the complex and violent entanglement of people and nature. Second, I show how a work of sound art by Sally Ann McIntyre, which is centred on the inaudible recordings of huia specimens played on Kapiti Island, the bird's original habitat, highlights that extinction results in the loss of multispecies relationality.